The Non-Interference of the Judiciary in Arbitral Proceedings in Peru - Taboada Mier, Jose Carlos (2025)
The principle of judicial non-interference in arbitration constitutes an essential safeguard to protect party autonomy and the effectiveness of arbitral proceedings. Its origin is linked to the nature of arbitration according to its historical background, including its materialization in the New York Convention and the UNCITRAL Model Law, instruments that inspired Peruvian legislation. This principle prevents the Judiciary from intervening during the development of arbitration, except in expressly regulated cases, such as assistance in evidence-taking or the enforcement of interim measures. Doctrine and the Constitutional Court’s jurisprudence have reaffirmed that judicial control must remain residual, exercised only through annulment or constitutional actions. In this way, non-interference ensures that the arbitration agreement retains its meaning, strengthening confidence in this mechanism of dispute resolution.